THE EFFECT OF GADGET USE INTENSITY DURING THE COVID-19 PANDEMIC ON EMOTIONAL INTELLIGENCE OF EARLY CHILDHOOD - Nurjanah, Ayu; Chairilsyah, Daviq; Solfiah, Yeni (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
The current development makes children no longer unfamiliar with gadgets. Gadget sophistication causes children to prefer to use it frequently, hence it inflicts an addiction effect. The covid-19 pandemic makes children tend to spend their time only using gadgets. This paper describes the effect of the intensity of applying gadgets during the covid-19 pandemic on the emotional intelligence of early childhood. This paper is a quantitative correlation research with a statistical test using Chi Schi-Square. The results indicate that the intensity of gadget use at TK Tembilahan is in the high category with a high percentage of 41%, medium percentage of 36%, and low percentage of 23%, and children's emotional intelligence is in the medium category with an empirical score of 19.10. It implies that there is a significant correlation between the significant intensity of gadget use during the covid-19 pandemic and the emotional intelligence of children aged 5-6 years at Kindergarten in Tembilahan.